Early insights into eyeblink conditioning using optically pumped magnetometer-based MEG - Lin, Chin-Hsuan Sophie; Tierney, Tim M.; Mellor, Stephanie; O’Neill, George C.; Bestmann, Sven; Barnes, Gareth R.; Miall, R. Chris (Frontiers in Human Neuroscience, 2025)
IntroductionThere is a profound lack of electrophysiological data from the cerebellum in humans, as compared to animals, because it is difficult to record cerebellar activity non-invasively using magnetoencephalography (MEG) or electroencephalography (EEG). Recent developments in wearable MEG sensors hold potential to overcome this limitation, as they allow the placement of sensors closer to the cerebellum.MethodsWe leveraged the development of wearable optically pumped magnetometers to record on-scalp MEG (OP-MEG) during an established cerebellar learning paradigm—eyeblink conditioning. In four healthy human adults, we first validated that OP-MEG can reliably detect cerebellar responses by examining responses to an air puff stimulus.ResultsSignificant responses were observed in sensors positioned over the cerebellar region in all four adults in response to the air puff. We then indirectly tested the hypothesis that these responses reflect the population-level spiking activity of Purkinje cells. The air-puff–evoked responses diminished during the acquisition of conditioned responses, corresponding with previously observed changes in Purkinje cell activity in animals. Additionally, in three out of four participants, we observed a cerebellar evoked response just prior to the peak of the conditioned blink, resembling learning-associated shifts in Purkinje cell response latencies.DiscussionThis study demonstrates that OP-MEG is a viable method for recording cerebellar activity in humans. By bridging invasive animal recordings with non-invasive human neuroimaging, these findings provide further evidence of the cerebellum’s role in human learning.